1987
DOI: 10.1620/tjem.153.111
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Branhamella catarrhalis adherence to oropharyngeal cells and seasonal incidence of lower respiratory tract infections.

Abstract: Bacterial colonization of the oropharynx is the initial event in most lower respiratory tract infections. To study the role of bacterial adherence in lower respiratory tract infections caused by Branhamella catarrhalis (B. catarrhalis) in winter, in vitro adherence assays of the organism to human oropharyngeal cells were carried out in winter, spring, summer and autumn. A total of 57 adults of both sexes were studied from January to December 1985. Forty eight persons of 57 had chronic pulmonary diseases and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Cells were collected, washed and counted as previously described (Mbaki et al 1987). Briefly, the oropharynx was vigorously scraped with a cotton-tipped swab.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were collected, washed and counted as previously described (Mbaki et al 1987). Briefly, the oropharynx was vigorously scraped with a cotton-tipped swab.…”
Section: Methodsmentioning
confidence: 99%
“…All of the CPD patients had chronic symptoms such as cough and sputum, and were moderately ill when symptoms were not aggravated; their frequent respiratory infections were determined to be caused by tion in the upper respiratory tract and nosocomial infection by P aeruginosa (10). We previously demonstrated, by investigating patients with CPD and age-matched controls, that increased adherence of B. catarrhalis to oropharyngeal cells was seen in patients with CPD and related to lower respiratory tract infections (13). The increased adherence of B. catarrhalis to oropharyngeal cells was not correlated with the age of the subjects but was correlated with the lung diseases in the patients (13).…”
Section: Methodsmentioning
confidence: 94%
“…Lower respiratory tract infections developed after bacterial colonization of the upper airways in compromised patients (7,9,12,13,23). Therefore, the investigation of bacterial binding to both upper and lower airway cells may provide clues to understanding the mechanism and pathogenesis of lower respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial adherence on the surface of oral mucosa has been regarded as an important factor for pathogenic bacteria to invade lower respiratory tract (Johanson et al 1979). It has been recently reported that there is a significant correlation between the occurrence of infection and the adherence ability of B, catarrhalis to oropharyngeal cells from patients with respiratory diseases (Mbaki et al 1987). Several investigators (Ninane et al 1978;Johnson et al 1981;Matsumoto 1981;McLeod et al 1983) reported that B. catarrhalis has become an important respiratory pathogen.…”
mentioning
confidence: 99%